Discover answers to your questions with Westonci.ca, the leading Q&A platform that connects you with knowledgeable experts. Explore thousands of questions and answers from a knowledgeable community of experts ready to help you find solutions. Join our Q&A platform to connect with experts dedicated to providing accurate answers to your questions in various fields.

if f(x) = 2x + 1 and g(x) = x2 find g (f(3))

Sagot :

Answer:

g(f(3)) = 49

Step-by-step explanation:

Evaluate f(3), then substitute the value obtained into g(x) , that is

f(3) = 2(3) + 1 = 6 + 1 = 7, then

g(7) = 7² = 49